THE RELATIONSHIP BETWEEN SEASON VARIATIONS AND DEPTH LEVEL ON THE GROWTH AND SURVIVAL RATE OF PEARL OYSTER SEEDS (Pinctada maxima) IN KAPONTORI BAY, BUTON ISLAND (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2014)
The pearl oyster (P. maxima) farming particularly in the Kapontori Bay, Buton Island waters and in other areas had complained for the mass mortality of pearl oysters saplings on the shell width between 3-4 cm. The mass mortality, was allegedly as a result of changing in environmental conditions and triggered by the shift in seasons. This research aimed to determine the effect of seasonal variations in water conditions at different depth levels on growth and survival of seedlings of pearl oysters conducted on March 27, 2007 to February 28, 2008. This research was very useful for pearl oyster farming in an effort to suppress the mass mortality rates based on the appropriate level of depth and seasons. The variance analyses showed that depth levels affected the survival rates of the pearl oyster seeds significantly (P